Engineering Responses to Climate Change: Proceedings of a Forum - National Academy of Engineering (The National Academies Press, 2022)
At the forum held during the 2021 annual meeting of the National Academy of Engineering, distinguished engineers gathered virtually to explore the roles that engineers can play in both mitigating and helping society adapt to climate change. Through a series of brief presentations and responses to questions from the moderator and the forum audience, the speakers discussed many of the issues at the forefront of climate-related engineering practice and policy today. This publication highlights the presentation and discussion of the event.

The Climate Change Educational Partnership: Climate Change, Engineered Systems, and Society: A Report of Three Workshops - National Academy of Engineering (The National Academies Press, 2014)
Societies develop engineered systems to address or mediate climate-related problems, such as drought, sea-level rise or wildfire control; the mediation involves public trust, public engagement, and governance. In these efforts, societies also decide - intentionally or implicitly - questions of justice and sustainability, such as what areas will receive mediation measures, what types of measures will be used, and what levels and kinds of local impacts are tolerated. In September 2010, the Center for Engineering, Ethics, and Society at the National Academy of Engineering began working with four other partners on a Climate Change Educational Partnership Phase I planning grant from the National Science Foundation. The project focused on defining and characterizing the societal and pedagogical challenges posed by the interactions of climate change, engineered systems and society, and identifying the educational efforts that a network could use to enable engineers, teachers, students, policymakers, and the public to meet the challenges. The project also aimed to build awareness of the complexities among a diverse set of communities affected by climate change and engineered systems and to engage the communities in addressing these challenges. The Climate Change Educational Partnership is the summary of three workshops convened over the course of the grant on the interactions of climate change with engineered systems in society and the educational efforts needed to address them. The first workshop provided the partners with an introduction to the varied social and technical dimensions found in the relationships among climate, engineered systems, and society. The second workshop built on the common language developed in the first. It allowed the partners to expand involvement in the project to include representatives from community and tribal colleges, professional societies and business. It examined the opportunities and challenges for formal and informal education, particularly in engineering classrooms and science museums, to prepare students and citizens to address these issues. The third workshop allowed the partners to broaden further the discussion and the audience. It solicited participation from government officials, Native American tribal representatives, professional society leaders, as well as educators, artists, scientists, and engineers who are developing programs that can manage change and educate students and citizens in ways that foster their leadership skills. The Climate Change Educational Partnership will be a useful resource to engineers, educators, corporate leaders, local and regional officials, members of professional societies, and others in their efforts to understand and address the challenges of climate change and its societal impacts.

Opportunities and Challenges for Digital Twins in Atmospheric and Climate Sciences: Proceedings of a Workshop—in Brief - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
The digital twin is an emerging technology that builds on the convergence of computer science, mathematics, engineering, and the life sciences. Digital twins have the potential to revolutionize atmospheric and climate sciences in particular, as they could be used, for example, to create global-scale interactive models of Earth to predict future weather and climate conditions over longer timescales. On February 1-2, 2023, the National Academies of Sciences, Engineering, and Medicine hosted a public, virtual workshop to discuss characterizations of digital twins within the context of atmospheric, climate, and sustainability sciences and to identify methods for their development and use. Workshop panelists presented varied definitions and taxonomies of digital twins and highlighted key challenges as well as opportunities to translate promising practices to other fields. The second in a three-part series, this evidence-gathering workshop will inform a National Academies consensus study on research gaps and future directions to advance the mathematical, statistical, and computational foundations of digital twins in applications across science, medicine, engineering, and society.

Surmounting the Barriers: Ethnic Diversity in Engineering Education: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Surmounting the Barriers: Ethnic Diversity in Engineering Education is the summary of a workshop held in September 2013 to take a fresh look at the impediments to greater diversification in engineering education. The workshop brought together educators in engineering from two- and four-year colleges and staff members from the three sponsoring organizations: the National Science Foundation, the National Academy of Engineering and the American Society for Engineering Education. While the goal of diversifying engineering education has long been recognized, studied, and subjected to attempted interventions, progress has been fitful and slow. This report discusses reasons why past recommendations to improve diversity had not been adopted in full or in part. Surmounting the Barriers identifies a series of key impediments, including a lack of incentives for faculty and institutions; inadequate or only short-term financial support; an unsupportive institutional and faculty culture and environment; a lack of institutional and constituent engagement; and inadequate assessments, metrics, and data tracking. The report also shares success stories about instances where barriers to diversity have been identified and surmounted, and the resources that could enable real solutions to implement steps toward progress.

Climate Change, the Indoor Environment, and Health - Institute of Medicine (The National Academies Press, 2011)
The indoor environment affects occupants' health and comfort. Poor environmental conditions and indoor contaminants are estimated to cost the U.S. economy tens of billions of dollars a year in exacerbation of illnesses like asthma, allergic symptoms, and subsequent lost productivity. Climate change has the potential to affect the indoor environment because conditions inside buildings are influenced by conditions outside them. Climate Change, the Indoor Environment, and Health addresses the impacts that climate change may have on the indoor environment and the resulting health effects. It finds that steps taken to mitigate climate change may cause or exacerbate harmful indoor environmental conditions. The book discusses the role the Environmental Protection Agency (EPA) should take in informing the public, health professionals, and those in the building industry about potential risks and what can be done to address them. The study also recommends that building codes account for climate change projections; that federal agencies join to develop or refine protocols and testing standards for evaluating emissions from materials, furnishings, and appliances used in buildings; and that building weatherization efforts include consideration of health effects. Climate Change, the Indoor Environment, and Health is written primarily for the EPA and other federal agencies, organizations, and researchers with interests in public health; the environment; building design, construction, and operation; and climate issues.

Practical Guidance on Science and Engineering Ethics Education for Instructors and Administrators: Papers and Summary from a Workshop December 12, 2012 - National Academy of Engineering (The National Academies Press, 2013)
Over the last two decades, colleges and universities in the United States have significantly increased the formal ethics instruction they provide in science and engineering. Today, science and engineering programs socialize students into the values of scientists and engineers as well as their obligations in the conduct of scientific research and in the practice of engineering. Practical Guidance on Science and Engineering Ethics Education for Instructors and Administrators is the summary of a workshop convened in December 2012 to consider best practices for ethics education programs in science and engineering. The workshop focused on four key areas: goals and objectives for ethics instruction, instructional assessment, institutional and research cultures, and development of guidance checklists for instructors and administrators. Leading experts summarized and presented papers on current research knowledge in these areas. This report presents the edited papers and a summary of the discussions at the workshop.

STEM Integration in K-12 Education: Status, Prospects, and an Agenda for Research - National Academy of Engineering; National Research Council (The National Academies Press, 2014)
STEM Integration in K-12 Education examines current efforts to connect the STEM disciplines in K-12 education. This report identifies and characterizes existing approaches to integrated STEM education, both in formal and after- and out-of-school settings. The report reviews the evidence for the impact of integrated approaches on various student outcomes, and it proposes a set of priority research questions to advance the understanding of integrated STEM education. STEM Integration in K-12 Education proposes a framework to provide a common perspective and vocabulary for researchers, practitioners, and others to identify, discuss, and investigate specific integrated STEM initiatives within the K-12 education system of the United States. STEM Integration in K-12 Education makes recommendations for designers of integrated STEM experiences, assessment developers, and researchers to design and document effective integrated STEM education. This report will help to further their work and improve the chances that some forms of integrated STEM education will make a positive difference in student learning and interest and other valued outcomes.

Ethics Education and Scientific and Engineering Research: What's Been Learned? What Should Be Done? Summary of a Workshop - National Academy of Engineering
Increasing complexity and competitiveness in research environments, the prevalence of interdisciplinary and international involvement in research projects, and the close coupling of commerce and academia have created an ethically challenging environment for young scientists and engineers. For the past several decades, federal research agencies have supported projects to meet the need for mentoring and ethics training in graduate education in research, often called training in the responsible conduct of research. Recently, these agencies have supported projects to identify ethically problematic behaviors and assess the efficacy of ethics education in addressing them. With support from the National Science Foundation, the National Academy of Engineering Center for Engineering, Ethics, and Society held the workshop \

Standards for K-12 Engineering Education? - National Research Council (The National Academies Press, 2010)
The goal of this study was to assess the value and feasibility of developing and implementing content standards for engineering education at the K-12 level. Content standards have been developed for three disciplines in STEM education–science, technology, and mathematic–but not for engineering. To date, a small but growing number of K-12 students are being exposed to engineering-related materials, and limited but intriguing evidence suggests that engineering education can stimulate interest and improve learning in mathematics and science as well as improve understanding of engineering and technology. Given this background, a reasonable question is whether standards would improve the quality and increase the amount of teaching and learning of engineering in K-12 education. The book concludes that, although it is theoretically possible to develop standards for K-12 engineering education, it would be extremely difficult to ensure their usefulness and effective implementation. This conclusion is supported by the following findings: (1) there is relatively limited experience with K-12 engineering education in U.S. elementary and secondary schools, (2) there is not at present a critical mass of teachers qualified to deliver engineering instruction, (3) evidence regarding the impact of standards-based educational reforms on student learning in other subjects, such as mathematics and science, is inconclusive, and (4) there are significant barriers to introducing stand-alone standards for an entirely new content area in a curriculum already burdened with learning goals in more established domains of study.

Successful K-12 STEM Education: Identifying Effective Approaches in Science, Technology, Engineering, and Mathematics - National Research Council
Science, technology, engineering, and mathematics (STEM) are cultural achievements that reflect our humanity, power our economy, and constitute fundamental aspects of our lives as citizens, consumers, parents, and members of the workforce. Providing all students with access to quality education in the STEM disciplines is important to our nation's competitiveness. However, it is challenging to identify the most successful schools and approaches in the STEM disciplines because success is defined in many ways and can occur in many different types of schools and settings. In addition, it is difficult to determine whether the success of a school's students is caused by actions the school takes or simply related to the population of students in the school. Successful K-12 STEM Education defines a framework for understanding \

Exploring Opportunities in Green Chemistry and Engineering Education: A Workshop Summary to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2007)

Engineering Societies and Undergraduate Engineering Education: Proceedings of a Workshop - National Academy of Engineering (The National Academies Press, 2017)
Engineering professional societies in the United States are engaged in a wide range of activities involving undergraduate education. However, these activities generally are not coordinated and have not been assessed in such a way that information about their procedures and outcomes can be shared. Nor have they been assessed to determine whether they are optimally configured to mesh with corresponding initiatives undertaken by industry and academia. Engineering societies work largely independently on undergraduate education, leaving open the question of how much more effective their efforts could be if they worked more collaboratively2014with each other as well as with academia and industry. To explore the potential for enhancing societies2019 role at the undergraduate level, the National Academy of Engineering held a workshop on the engagement of engineering societies in undergraduate engineering education. This publication summarizes the presentations and discussions from the workshop.

Novel Processes for Advanced Manufacturing: Summary of a Workshop - National Research Council
The Standing Committee on Defense Materials Manufacturing and Infrastructure (the DMMI standing committee) of the National Materials and Manufacturing Board of the National Research Council (NRC) held a workshop on December 5 and 6, 2012, to discuss new and novel processes in industrial modernization. The participants of the workshop provided their individual opinions but no recommendations were developed as a result of the workshop. The workshop focused on Additive manufacturing, electromagnetic field manipulation of materials, and design of materials. Additive manufacturing is the process of making three-dimensional objects from a digital description or file. The workshop addresses different aspects of additive manufacturing including surface finish and access to manufacturing capabilities and resources. Electromagnetic field manipulation of materials is the use of electric and\/or magnetic fields to change the mechanical or functional properties of a material or for the purposes of sintering. The workshop examined research prioritization in this area as well as other objectives. \

Big Data in Materials Research and Development: Summary of a Workshop - National Research Council (The National Academies Press, 2014)
Big Data in Materials Research and Development is the summary of a workshop convened by the National Research Council Standing Committee on Defense Materials Manufacturing and Infrastructure in February 2014 to discuss the impact of big data on materials and manufacturing. The materials science community would benefit from appropriate access to data and metadata for materials development, processing, application development, and application life cycles. Currently, that access does not appear to be sufficiently widespread, and many workshop participants captured the constraints and identified potential improvements to enable broader access to materials and manufacturing data and metadata. This report discusses issues in defense materials, manufacturing and infrastructure, including data ownership and access; collaboration and exploitation of big data's capabilities; and maintenance of data.

Rising Above the Gathering Storm: Developing Regional Innovation Environments: Summary of a Workshop - National Academy of Sciences; National Academy of Engineering; Institute of Medicine
In October 2005, the National Academy of Sciences, National Academy of Engineering, and Institute of Medicine released a policy report that served as a call to action. The report, Rising Above the Gathering Storm: Energizing and Employing America for a Brighter Economic Future observed that \

Summary of the Workshop on Structural Nanomaterials - National Research Council
This report provides a summary of the workshop put together by the National Materials Advisory Board which covered the following areas: synthesis and assembly of nanomaterial building blocks, characterization of nanomaterials, examples of structural nanomaterials currently in use, potential applications of nanomaterials, gaps in understanding of synthesis, assembly, chemical, and physical characterization and the need for interdisciplinary approach, as well as identification of the \

Engineering in K-12 Education: Understanding the Status and Improving the Prospects - National Academy of Engineering; National Research Council (The National Academies Press, 2009)
Engineering education in K-12 classrooms is a small but growing phenomenon that may have implications for engineering and also for the other STEM subjects2014science, technology, and mathematics. Specifically, engineering education may improve student learning and achievement in science and mathematics, increase awareness of engineering and the work of engineers, boost youth interest in pursuing engineering as a career, and increase the technological literacy of all students. The teaching of STEM subjects in U.S. schools must be improved in order to retain U.S. competitiveness in the global economy and to develop a workforce with the knowledge and skills to address technical and technological issues. Engineering in K-12 Education reviews the scope and impact of engineering education today and makes several recommendations to address curriculum, policy, and funding issues. The book also analyzes a number of K-12 engineering curricula in depth and discusses what is known from the cognitive sciences about how children learn engineering-related concepts and skills. Engineering in K-12 Education will serve as a reference for science, technology, engineering, and math educators, policy makers, employers, and others concerned about the development of the country's technical workforce. The book will also prove useful to educational researchers, cognitive scientists, advocates for greater public understanding of engineering, and those working to boost technological and scientific literacy.

Advancing Diversity in the US Industrial Science and Engineering Workforce: Summary of a Workshop - National Academy of Engineering (The National Academies Press, 2014)
Thousands of gifted individuals, including women and underrepresented minorities, remain a disproportionally small fraction of those in science, technology, engineering, and math (STEM) careers. Industry, as the largest employer category of those with STEM backgrounds, stands to benefit considerably from greater inclusion of women and underrepresented minorities in the workforce. However, nothing short of a game-changing environment must be created to harness the talent of those not fully represented in the STEM workforce. Advancing Diversity in the US Industrial Science and Engineering Workforce is the summary of a workshop held in May, 2012 by the National Academy of Engineering, focusing on the needs and challenges facing industry in particular, and it is intended to facilitate further discussion and actions to address these complex issues. The workshop provided a forum for leaders from industry, academia, and professional associations to share best practices and innovative approaches to recruiting, retaining, and advancing women and underrepresented minorities in the scientific and engineering workforce throughout the nation's industries.

The Global Movement and Tracking of Chemical Manufacturing Equipment: A Workshop Summary - National Research Council (The National Academies Press, 2014)
Dual-use applications for chemical manufacturing equipment have been recognized as a concern for many years, and export-control regulations worldwide are in place as a result. These regulations, in conjunction with the verification and inspection requirements of Article VI of the Chemical Weapons Convention, are designed to support non-proliferation of manufacturing equipment suitable for production of chemical warfare agents. In recent years, globalization has changed the distribution of chemical manufacturing facilities around the world. This has increased the burden on current inspection regimes, and increased the amount of manufacturing equipment available around the world. Movement of that equipment, both domestically and as part of international trade, has increased to accommodate these market shifts. To better understand the movement and tracking of chemical manufacturing equipment of dual-use concern, the Project on Advanced Systems and Concepts for Countering Weapons of Mass Destruction at the Naval Postgraduate School contracted with the Board on Chemical Sciences and Technology of the National Research Council to hold a workshop on the global movement and tracking of chemical manufacturing equipment. The workshop, held in May 2014, looked at key concerns regarding the availability and movement of equipment for chemical manufacturing, particularly used and decommissioned equipment that is of potential dual-use concern. The workshop examined today's industrial, security, and political contexts in which these materials are being produced, regulated, and transferred. The workshop also facilitated discussions about current practices, including consideration of their congruence with current technologies and security threats in the global chemical industrial system. The Global Movement and Tracking of Chemical Manufacturing Equipment summarizes the presentations and discussion of the event.

Best Practices in Assessment of Research and Development Organizations: Summary of a Workshop - National Research Council (The National Academies Press, 2012)
The National Institute of Standards and Technology (NIST)–recognizing that information and insights gained through continual examination of practices for organizational assessment are useful for decision makers at organizations across the deferral, industrial, academic, and national laboratory sectors-recently requested that the National Research Council (NRC) organize a panel to review best practices in assessment of research and development (R&D) organizations. In response, the NRC established the Panel for Review of Best Practices in Assessment of Research and Development Organizations. The panel was charged to consider means of assessing the following in a manner that satisfies the requirements of NIST to perform effective assessments but also identifies assessment methods that can be applied selectively to other R&D organizations. These methods include: technical merit and quality of the science and engineering work, the adequacy of the resources available to support high-quality work, the effectiveness of the agency's delivery of the services and products required to fulfill its goals, the degree to which the agency's current and planned R&D portfolio supports its mission, as well as the agency's flexibility to respond to changing economic, political, social and technological contexts. As one means of data gathering, among others that the panel is performing toward development of a final report of its findings, the panel organized a planning committee for a workshop on best practices in assessment of R&D organizations. Best Practices in Assessment of Research and Development Organizations: Summary of a Workshop reviews the workshop conducted at the Keck Center of the National Academies in Washington, D.C., on March 19, 2012.